“She couldn’t simply write a letter.” Scenes of Reading in Ingeborg Bachmann’s The Book of Franza (Konturen, 2019)
This article contends that Ingeborg Bachmann’s The Book of Franza anticipates and significantly advances feminist critiques of writing and authorship by exposing and effectively deconstructing scenes of reading as the site where discursive power is exercised and significations are enforced by using “her” as a universal signifier. But it also performs a refusal to impart to the reader a subject that could be pinned down, identified, and hence objectified. Eluding containment by the patriarchal law, the subject has the chance to come into a law of its own as it vanishes and subsequently returns as a reader with a new type of leverage.